Direct Study of CO2 Capture Efficiency during Microalgae Arthrospira platensis Cultivation at High CO2 Concentrations - Chunzhuk E.A. (2023)
© 2023 by the authors.Direct study of CO2 capture efficiency during microalgae Arthrospira platensis cultivation at high CO2 concentrations was carried out. Microalgae were grown in a 90 L photobioreactor on Zarrouk’s medium prepared with distilled water. Three 15-day experiments were carried out with different initial CO2 concentrations: 1, 5, and 9 vol.%. During the experiments, both the change in the optical density of the microalgae suspension and the direct change in the CO2 concentration in the chamber were measured. The maximum decrease in CO2 concentration due to the growth of microalgae was 0.10 vol.% (CO2)/day in the experiment with an initial CO2 concentration of 5 vol.%. Growth rate of biomass density was 79.4, 76.3, and 48.4 (mg/L)/day at 1, 5, and 9 vol.% CO2 concentrations, respectively. During the experiment with initial CO2 concentrations of 1 and 5 vol.%., pH of the culture medium was increased, but pH was decreased from 9.2 to 8.8 at 9 vol.%. In general, good viability (high quality of biomass and high rate of its growth) of Arthrospira platensis was established at 1 and 5 vol. (CO2)%, while massive death of Arthrospira platensis cells was observed in the experiment with 9 vol. (CO2)%. Biochemical analysis of the resulting biomass revealed a decrease in the content of lipids and proteins with an increase in CO2 concentration.